S14 The role of soluble urokinase plasminogen activating receptor (suPAR) in parapneumonic effusions. (12th November 2019) - Arnold, DT; Hamilton, FW; Elvers, KT; Zahan-Evans, N; Maskell, NA
Abstract : Introduction: For decades the management of parapneumonic effusions has relied on pleural fluid pH measurement. However, the eventual requirement for fibrinolytics or surgery is more often dictated by the development of loculations. soluble urokinase Plasminogen Activating Receptor (suPAR) is a novel biomarker released by pleural mesothelial cells in response to infection as part of the fibrinolysis cascade. This study assessed levels of suPAR in the pleural fluid (PF) and serum of patients with parapneumonic effusions. Methods: We analysed stored serum and PF from a prospectively collected cohort of patients with effusions due to infection. Cases with frank pus on thoracentesis were excluded. Baseline pleural ultrasounds were performed to assess loculations, with routine bloods and pleural fluid analysis. Clinical outcomes and final diagnoses were confirmed at 12 months by two respiratory consultants. suPAR levels were analysed in duplicate using the suPARnostic® double monoclonal antibody sandwich ELISA assay. Binomial logistic regression was used to compare clinical outcomes to biochemical markers. Mann Whitney test was used to compare suPAR levels between groups. Results: Between 2008 and 2016 there were 93 patients with parapneumonic effusions recruited (49 non-loculated and 44 loculated effusions). Median PF suPAR was 88ng/ml (9–614ng/ml). PF suPAR was significantly higher in loculated effusions (median 162ng/ml versus 22ng/ml, p<0.001) see figure 1. Serum suPAR did not correlate with PF suPAR nor clinical outcomes. The sensitivity and specificity of PF suPAR >35ng/ml to predict loculations was 100% and 91% respectively. 94% of patients (45/48) with a pf suPAR over 35ng/ml were managed with a chest tube. Using stepwise logistic regression (in a model that included PF pH) PF suPAR was an independent predictor of need for fibrinolytics and surgery (p<0.001). Conclusion: The development of loculations is an important differentiator in the management of parapneumonic effusions. suPAR is a novel biomarker and is part of the fibrinolysis cascade. This is the first study to assess the potential role of suPAR in parapneumonic effusions. PF suPAR was superior to PF pH and serum CRP at predicting loculations as well as requirement for fibrinolytics or surgery. Its true utility needs assessing in a larger prospective study.